DYNAMICS AND CONCEPT OF THE ROLE OF LAW IN SUSTAINABLE DEVELOPMENT - Loso Judijanto; Rabith Madah Khulaili Harsya; Arief Fahmi Lubis (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The concept behind meeting current sustainable development aims to meet needs without endangering the capacity of future generations to meet their own. In this sense, ensuring the achievement of sustainable development goals depends heavily on legislation. The application of sustainable development and its encouragement are greatly aided by the law. Through appropriate regulations, effective law enforcement, and the application of principles of justice, law can be a main pillar in achieving development objectives that prioritize not just economic advancement but also environmental preservation and social welfare for future generations. Overall, the role of law in sustainable development is crucial. Law not only regulates but also protects the rights of the community and the environment, and ensures that development is carried out in a sustainable and responsible manner. With a strong legal framework, Indonesia can achieve sustainable development goals that balance economic, social, and environmental needs.